PENGGUNAAN TEKNOLOGI CHATGPT TERHADAP EFISIENSI PENYELESAIAN TUGAS KARYA ILIMIAH DI KALANGAN MAHASISWA (MAHASISWA UIN SUNAN KALIJAGA) - Nursafitri, Riski; Sabarudin; Nur Munajat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of ChatGPT as a tool in completing students' scientific work is increasingly popular. This study aims to analyze the extent to which ChatGPT can improve the efficiency of the scientific paper writing process. The research method used is a quantitative method through survey techniques for students of the Faculty of Tarbiyah and Teacher Training from the PAI, Chemistry, Biology, Arabic, PGSD and PIAUD study programs at the 3rd semester level with a total of 43 respondents who have used ChatGPT. The results of this study show that ChatGPT technology is effective as a tool in completing scientific work tasks, ChatGPT can significantly speed up the process of data collection, framework writing. However, behind the rapid development of the use of CHatGPT, it is also necessary to understand the resulting information crisis to avoid academic violations, plagiarism, and scientific errors, even though ChatGPT technology in the world of education is still debated. However, it is necessary to anticipate and manage its negative impact, especially in the academic world.